The Interrelation of Balaghah and Egypt: Study of Amin al-Khuli's Thought - Syihabuddin, Muhammad; Manggala, Kayan; Nurkholisoh, Siti; Ansharah, Indana Ilma (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
The essence of the science of Balaghah has been ingrained in the Arabic language to achieve creativity in both poetry and other literary forms. Al-Khuli in his book "Manahij Tafsir" explains that the many links between Egypt and Balaghah form an intense interrelationship. This article seeks to uncover the forms of a historical overview of Egypt and its influence on the science of Balaghah. This research uses a descriptive qualitative method through the main source of Amin al-Khuli's book "Manahij Tajdid fi al-Nahw wa al-Balaghah wa al-Tafsir wa al-Adab" and some relevant articles. In analyzing the data, researchers went through several stages, namely; identification, categorization, concept-historical content analysis, and ended with interpretation-validation. The results of this article reveal that: 1) Egypt has a strong character both in terms of geographical and social ideals. 2) Egypt became the foothold of prominent Balaghah figures who came from various regions. 3) There are two schools in Balaghah namely kalamiyyah and adabiyyah. 4) Egypt had a huge impact on the development of Arabic literature, which the Egyptians themselves put their literary knowledge as a form of dedication and love of harmony, as well as a form of devotion to the Qur'an. The above points summarize that Balaghah and Egypt have a close relationship that is inseparable in terms of history. Abstrak Esensi ilmu Balaghah telah mandarah daging dalam bahasa Arab untuk mencapai kreativitas baik puisi maupun bentuk sastra lainnya. Al-Khuli dalam kitabnya “Manahij Tafsir” menjelaskan bahwa banyak keterkaitan antara Mesir dan Balaghah membentuk interelasionalitas yang intens. Artikel ini ingin mencoba mengungkap bentuk-bentuk tinjauan historis mengenai Mesir dan pengaruhnya terhadap ilmu Balaghah. Penelitian ini menggunakan metode deskriptif kualitatif melalui sumber utama kitab karya Amin al-Khuli berjudul Manahij Tajdid fi al-Nahw wa al-Balaghah wa al-Tafsir wa al-Adab, dan beberapa artikel relevan. Dalam menganalisa data, peneliti melewati beberapa tahapan yaitu; identifikasi, kategorisasi, analisis konten konsep-historis, dan diakhiri dengan interpretasi-validasi. Hasil artikel ini mengungkap bahwa: 1) Mesir memiliki tabiat kuat baik dari segi keidealan secara geografis dan sosial. 2) Mesir menjadi pijakan tokoh-tokoh Balaghah terkemuka yang berasal dari berbagai wilayah. 3) Terdapat dua aliran dalam Balaghah yaitu kalamiyyah dan adabiyyah. 4) Mesir memiliki dampak yang sangat besar bagi perkembangan sastra Arab, yang mana orang-orang Mesir sendiri meletakkan keilmuan sastranya sebagai bentuk dedikasi dan kecintaan pada keharmonian, juga bentuk pengabdian pada al-Qur’an. Berbagai poin di atas menjadi rangkman, bahwa Balaghah dan Mesir memiliki hubungan erat yang tak terpisahkan dari sisi sejarahnya.